Les documents copto-arabes dans les archives chrétiennes d’Éthiopie : de rares témoins de l’autorité épiscopale (XIVe-XVe s.) - Anaïs Wion (Afriques)
The Orthodox Christian Church of Ethiopia was statutorily a Coptic bishopric. From the fourth century until the middle of the twentieth century, its metropolitan bishops were appointed by the Patriarchal See of Alexandria. Three Copto-Arabic documents, issued between 1375 and 1424 by Egyptian bishops in Ethiopia, provide a better understanding of the power relation issues between the Coptic episcopate, the Ethiopian political power, and the powerful monastic networks of the Ethiopian Orthodox Church. Did abuna Salāmā, the “Translator”, plot with the monks of Ḥayq Esṭifānos to place Dāwit on the throne? What accounts for his successor, abuna Bartalomēwos, first a faithful ally to the throne, ending up placed under close surveillance and then dismissed and imprisoned? Did an Egyptian bishop, whose seat was in the Nile delta, “take his place” after seeking asylum in Ethiopia? In the wake of the shift in the power relations woven between Alexandria and Ethiopia, how come two Egyptian metropolitans endorsed all religious decisions, even the least orthodox ones, taken by King Zar’ā Yā‘eqob? Analysing these documents enables one to raise, and sometimes answer, these questions. It is also an opportunity to take a new look at administrative scriptural practices.